Protectin DX Attenuates Lumbar Radicular Pain of Non-compressive Disc Herniation by Autophagy Flux Stimulation via Adenosine Monophosphate-Activated Protein Kinase Signaling - Zhao, Qing-xiang; Wang, Yi-hao; Wang, Si-cong; Xue, Song; Cao, Zhen-xin; Sun, Tao (Frontiers in Physiology, 2022)
Background: Neuroinflammation plays a crucial role in initiating and sustaining lumbar radicular pain (LRP). Protectin DX (PDX) has been experimentally verified to possess pro-resolving properties and anti-inflammatory effects. This study aimed to observe the analgesic effects of PDX and its potential mechanisms in rats with LRP with non-compressive lumbar disc herniation (NCLDH). Method: Rat models of NCLDH were established, and rats were randomly divided into four groups: the sham group, the vehicle group, the PDX (10 ng PDX) group, and the PDX (100 ng PDX) group. Changes in the mechanical withdrawal threshold and thermal withdrawal latency were observed for 7 days. The mRNAs of pro-inflammatory and anti-inflammatory mediators were evaluated via real time-polymerase chain reaction, whereas western blot and immunohistochemistry were separately conducted to assess the expression levels of autophagy-related proteins and adenosine monophosphate-activated protein kinase (AMPK) signaling. Results: Intrathecal delivery of PDX suppressed interleukin (IL)-6 and IL-1β mRNA levels and facilitated mRNA transcription of transforming growth factor-β1, with attenuation of hyperalgesia in LPR rat models. With the application of nucleus pulposus to the dorsal root ganglion, autophagy flux and AMPK signaling were severely disrupted in the spinal dorsal horns, and intrathecal treatment with PDX could dose-dependently restore the dysfunction of autophagy flux and AMPK signaling. Conclusions: These data suggest that PDX possesses pro-resolving properties and exerts potent analgesic effects in LRP by affecting autophagy flux via AMPK signaling.